2021
DOI: 10.1177/1745691621998326
|View full text |Cite
|
Sign up to set email alerts
|

Are Regional Differences in Psychological Characteristics and Their Correlates Robust? Applying Spatial-Analysis Techniques to Examine Regional Variation in Personality

Abstract: There is growing evidence that psychological characteristics are spatially clustered across geographic regions and that regionally aggregated psychological characteristics are related to important outcomes. However, much of the evidence comes from research that relied on methods that are theoretically ill-suited for working with spatial data. The validity and generalizability of this work are thus unclear. Here we address two main challenges of working with spatial data (i.e., modifiable areal unit problem and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 124 publications
(184 reference statements)
6
60
1
Order By: Relevance
“…We examined associations between state-level Big Five traits and vaccination rates using a series of multiple regressions. Because the independence-of-errors assumption is often violated using geographic data, we controlled for spatial dependence among the 48 contiguous U.S. states by using spatial regression (Ebert et al, 2021;Ward & Gleditsch, 2008). Thus, we used a binary adjacency matrix (https://osf.io/5nz6t; Webster et al, 2021) that reflected which 48 states shared land or water borders to create spatial lag variables for both vaccination rate outcomes.…”
Section: Data Analysis and Powermentioning
confidence: 99%
“…We examined associations between state-level Big Five traits and vaccination rates using a series of multiple regressions. Because the independence-of-errors assumption is often violated using geographic data, we controlled for spatial dependence among the 48 contiguous U.S. states by using spatial regression (Ebert et al, 2021;Ward & Gleditsch, 2008). Thus, we used a binary adjacency matrix (https://osf.io/5nz6t; Webster et al, 2021) that reflected which 48 states shared land or water borders to create spatial lag variables for both vaccination rate outcomes.…”
Section: Data Analysis and Powermentioning
confidence: 99%
“…In a first analytic step, we mapped out the spatial distributions for both regional personality and regional prototypical spending (see Figure 2) using Actor-Based Clustering (Brenner, 2017; Buecker, Ebert, Götz, Entringer, & Luhmann, 2020; Ebert, Gebauer, et al, 2019). Actor-Based Clustering is a statistical approach that utilizes the finest geographical information available to reveal areas where high or low values of a variable cluster geographically (see for further details).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we estimated the spatial autocorrelation among error terms and found significant positive spatial autocorrelation of small to medium sized magnitude for four of the five traits (Table 1, column 2). For these four traits (all except for conscientiousness), we fitted additional models that included spatially lagged scores of the dependent variable as an additional predictor (Ebert, Gebauer, et al, 2019). Including these spatial lags successfully captured any existing spatial dependencies among error terms (Table 1, column 4).…”
Section: Regional Personality Predicts Regional Spending (Hypothesis 1)mentioning
confidence: 99%
“…Fourth, cultural differences can exist at multiple geographical levels (Cohen, 2009; Ebert et al, in press). We wanted to ensure that our results (as hypothesized) reflect local cultural shifts and are not driven by overlapping trends at broader geographical levels.…”
Section: Resultsmentioning
confidence: 99%
“…After completing the survey, participants received a customized evaluation of their personality. The psychometric suitability of the GPIPP personality data for cross-regional research has extensively been demonstrated elsewhere (Ebert et al, in press; Rentfrow et al, 2008).…”
Section: Methodsmentioning
confidence: 92%